CD40–CD40L: Linking pancreatic, adipose tissue and vascular inflammation in type 2 diabetes and its complications. (March 2013) - Seijkens, Tom; Kusters, Pascal; Engel, David; Lutgens, Esther
Numerous epidemiological studies have consistently demonstrated the strong association between type 2 diabetes mellitus (T2DM) and an increased risk to develop cardiovascular disease. The pathogenesis of T2DM and its complications are characterized by pancreatic, adipose tissue and vascular inflammation. CD40 and CD40L, members of the tumour necrosis factor (receptor) TNF(R) family, are well known for their role in immunity and inflammation. Here we give an overview on the role of CD40–CD40L interactions in the pathogenesis of T2DM with a special focus on pancreatic, adipose tissue and vascular inflammation. In addition, we explore the role of soluble CD40L (sCD40L) as a potential biomarker for the development of cardiovascular disease in T2DM subjects. Finally, the therapeutic potential of CD40–CD40L inhibition in T2DM is highlighted.